PHYTOCHEMICAL SCREENING, TOXICITY AND ANTI-BACTERIAL ASSAY FROM STEM-BARK EXTRACTS OF Garcinia celebica and G. tetandra - Yuliasri Jamal; Andria Agusta (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2001)
Garcinia is proven to have multi benefit in curing various deseases, some have edible fruit and edible oil. This experiment was a preliminary analysis, including phytochemistry screening, toxicity and antibacterial tests of stem-bark G. celebica and G. tetandra extracts. Ether, ethanol and water extracts of both Garcinia contained 19 different chemical components. Hexane, methanol and water extracts stem-bark of both Garcinia extracts were found to have toxicological effect on Artemisia salina larva with the highest LC50 of G. celebica water extract. Dichloromethane-methanol 1:1 extract of G. celebica acted as growth inhibition on Gram positive and Gram negative bacteri , while the extract of G. tetandra could only inhibit the growth of Gram negative bacterium. Comparing with erythromycin and novobiosin antibiotics, the inhibiton growth activity of the two Garcinia extracts were lower than those of antibiotics.Key words: Garcinia, phytochemical screening, toxicological effect, anti-bactery